Effect of COVID-19 Pandemic on Psychological Attitudes’ for Nurse Workers at Isolation Hospitals in Baghdad City - Ahmad Shihab Ahmad (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: to identify the effect of COVID 19 pandemic psychological attitudes for nurses’ workers atIsolation Hospitals in BaghdadMethodology: descriptive study conducted among 100 nurses selected by purposive sample. The datacollected by using electronic questionnaire related to psychological attitudes composed of 10 items and 3items related to demographic characteristics.Results: the result reflects that most of nurses are males and at age (20-29) years, also they are graduatedfrom high school of nursing and nursing college. Most of nurses’ psychological status effected by COVID,they are feel anxiety stress depression and frustration due to un familiar area, lack of experience, un effectedtreatment, COVID 19 bad news, long working time and isolation from friends. There is significant correlationbetween nurses’ psychological attitude and level of education.Conclusion: COVID 19 effect on the nurses’ psychological status. Therefore, it is important to initiatetraining session to educate nurses about stress management, how to deal with psychological problems andadapt with different situation